2022
DOI: 10.3390/cancers14163960
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, Treatments, and Survival of Uveal Melanoma: A Comparison between Chinese and American Cohorts

Abstract: Uveal melanoma (UM) is the most common intraocular malignant carcinoma. This study aimed to compare the clinical features, treatment modalities, and prognosis of UM patients in China with those in America over a 15-year period. In the study, 4088 American patients with primary UM from the Surveillance, Epidemiology, and End Results (SEER) database and 1508 Chinese patients from Tongren-ophthalmology Research Association of Clinical Evaluation (TRACE) were included. Univariable and multivariable analyses were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
(38 reference statements)
1
3
0
Order By: Relevance
“…The mean age at the time of diagnosis varied between 59.61 years and 64.26 years during the analysed period, and these results were similar to those reported in the USA (60 years) [32], Ireland (61 years) [30], Canada (61.5 years) [38], Australia (62.8 years) [26], England (64 years) [15], and Sweden (66.0 years) [24], but higher than in China (62.8 years) [41]. The peak incidence of UM was at 60-69 years in Hungary, which is slightly lower than the ages reported in England, the USA (70-79 years) [15,32], and Sweden (75-84 years) [14].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The mean age at the time of diagnosis varied between 59.61 years and 64.26 years during the analysed period, and these results were similar to those reported in the USA (60 years) [32], Ireland (61 years) [30], Canada (61.5 years) [38], Australia (62.8 years) [26], England (64 years) [15], and Sweden (66.0 years) [24], but higher than in China (62.8 years) [41]. The peak incidence of UM was at 60-69 years in Hungary, which is slightly lower than the ages reported in England, the USA (70-79 years) [15,32], and Sweden (75-84 years) [14].…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, nitric oxide synthase expression is associated with poor prognosis and reduced survival in UM [ 49 ]. Despite improvements in treatment options, five-year disease-specific survival remains unchanged, as reported in the USA (80.9%) between 1973 and 2013 [ 50 ], Australia (81%) between 1982 and 2015 [ 27 ], Northern Ireland (82.6%) in 2016 [ 28 ], and China (86.6%) [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we observed that the age at diagnosis of UM in ethnic groups in NZ with more pigmented skin and iris color (Māori, Asians, and Pacific Peoples) was younger than in European ethnicities. Elsewhere, lower age at UM presentation has also been noted in Asian, Black, Pacific, and Hispanic populations 1,33,38–40 . Māori are NZ indigenous population that has origins from Southeast Asia, Melanesia, and Polynesia, as discovered via genetic analysis 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere, lower age at UM presentation has also been noted in Asian, Black, Pacific, and Hispanic populations. 1,33,[38][39][40] Māori are NZ indigenous population that has origins from Southeast Asia, Melanesia, and Polynesia, as discovered via genetic analysis. 41 Given the ancestry, it is likely that the earlier age at diagnosis observed in our Māori population may be related to underlying genetic similarities to the Asian and Pacific cohorts above, and thus similarities in the earlier presentation with UM.…”
Section: Discussionmentioning
confidence: 99%